2020
DOI: 10.1186/s41938-020-00224-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan and emamectin benzoate on the reproductive system of Eobania vermiculata (Muller) land snails

Abstract: The reproductive system of snails represents essential organ that affects snail population size. Therefore, the present research was directed to evaluate the effect of two biopesticides chitosan (Ch) and emamectin benzoate (EMB) LC 50 on the reproductive system of Eobania vermiculata (Muller). Land snails were treated using thin-film layer technique. Snails were dissected and organs of reproductive system were weighted and examined for any pathological changes at 24, 48 and 72 h post treatment. Moreover, stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…EMB, an avermectin, has the potential to intoxicate insects via ingestion as well as contact 44,45 . The obtained data clearly indicate that EMB contact toxicity is lethal to T. pisana and corroborate the results of Kandil et al 24 . who, using a residual film technique, found a 72‐h median lethal concentration (LC 50 ) of 120.13 μg cm −2 for EMB against Massylaea vermiculata (Syn: Eobania vermiculata ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…EMB, an avermectin, has the potential to intoxicate insects via ingestion as well as contact 44,45 . The obtained data clearly indicate that EMB contact toxicity is lethal to T. pisana and corroborate the results of Kandil et al 24 . who, using a residual film technique, found a 72‐h median lethal concentration (LC 50 ) of 120.13 μg cm −2 for EMB against Massylaea vermiculata (Syn: Eobania vermiculata ).…”
Section: Discussionsupporting
confidence: 89%
“…42,43 EMB, an avermectin, has the potential to intoxicate insects via ingestion as well as contact. 44,45 The obtained data clearly indicate that EMB contact toxicity is lethal to T. pisana and corroborate the results of Kandil et al 24 who, using a residual film technique, found a 72-h median lethal concentration (LC 50 ) of 120.13 μg cm −2 for EMB against Massylaea vermiculata (Syn: Eobania vermiculata). Poison bait treatment with EMB under shade-net conditions has also been shown to be highly effective against the slug, Filicaulis alte, recording an average of 10.50 dead slugs per plot.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There was a marked increase in the size of the ovotestis number of oocytes in Achatina fulica snails injected with estradiol and progesterone ( Kruatrachue et al., 1996 ). Chitosan and emamectin benzoate caused prevention of egg production in treated E. vermiculata snails ( Patel et al., 2016 ; Kandil et al., 2020 ). Finally, the squeaky decreases of the tested reproductive hormones levels, malformations of sperms and ova and complete egg cessation at the third week after treatment of snails with contraceptive pills as baits may assure the efficacy of this method in controlling high population densities of E. vermiculata devouring citrus trees at Sharkia Governorate, Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…2 cm 3 of each prepared NPs with concentrations 250, 500, 750, and 1000 ppm were added to Petri dish (9 cm in diameter), keeping the gentle moving of the dish in regular circles until the perfect distribution of TiO 2 -based NPs. 17 The snails were added after complete evaporation of the solvent at room temperature within 5 min, leaving the previous thin layer. For 7 days, 10 adult individual snails were exposed to various concentrations of nanomaterials.…”
Section: Methodsmentioning
confidence: 99%